Dissipation of four fungicides on greenhouse strawberries and an assessment of their risks. (September 2015) - Wang, Zhiwei; Cang, Tao; Qi, Peipei; Zhao, Xuepin; Xu, Hao; Wang, Xiangyun; Zhang, Hu; Wang, Xinquan
Abstract: Risk assessments of the fungicides pyraclostrobin, iprodione, tebuconazole and cyprodinil were carried after determining their persistence on strawberries following two applications by spraying in a greenhouse. The Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method was used for sample preparation, and high-performance liquid chromatography-tandem mass spectrometry and gas chromatography-tandem mass spectrometry were used for sample analysis. The range for the average recoveries of the four fungicides was 86.2–105.4 %, and the relative standard deviation range was 2.7–6.1 %. The half-lives of pyraclostrobin, iprodione, tebuconazole and cyprodinil after a single application were 3.7, 3.6, 3.3 and 2.8 d, respectively. Compared with a single application, a second application of the fungicides increased the average concentrations of residues left on the strawberries. Risk assessments of the four fungicides were conducted by comparing national estimated daily intakes against acceptable daily intakes under good agricultural practice conditions. With application at the recommended dosage, strawberries sprayed with pyraclostrobin, iprodione and tebuconazole were safe for consumption after two applications. By contrast, while the first application of cyprodinil was safe, the second presented a high health risk. Even at the recommended dosage (720 a. i. g ha-1), repeat applications of cyprodinil should be banned. Highlights: Residues of four fungicides on strawberries after two applications are investigated. The QuEChERS method is coupled with GC-MS-MS or HPLC-MS-MS for sample analysis. Strawberries sprayed with pyraclostrobin, iprodione or tebuconazole present low health risk. Repeat application of cyprodinil presents a high health risk.